Procedure optimization for concentration and detection of protozoa and helminths in great volumes of water - RÃos Tobón, Sandra; López Jiménez, Juliana; Campo Polanco, Laura Francisca; Agudelo Cadavid, Ruth Marina; Gutiérrez Builes, Lina Andrea (Revista Cubana de Medicina Tropical, 2017)
Feces-contaminated water is a vehicle of transmission of potentially pathogenic microorganisms responsible for illnesses that represent main causes of death worldwide. A protocol for detection of intestinal parasites in great volumes of water was optimized. It includes: membrane filtration, mechanical agitation with detergent, centrifugation, chemical concentration with Mini Parasep® and microscopic examination. From samples of feces-contaminated water containing parasitic forms, a total recovery percentage of 85.7 % of parasites was achieved after tests. This procedure provides a useful alternative method that could be subjected to validation as a routine methodology in the diagnosis of microbiological water quality.